(Dis)affordances and abandonment - Katarina Winter; Klara Hermansson (Sociologisk Forskning)
In recent decades, numerous security technologies have emerged with the aim of fostering secure communities and providing people with the tools to bolster their everyday safety. Focusing specifically on security apps, this article explores how apps addressing security in public and semi-public spaces constitute preconditions for everyday user engagement, and vice versa, how users actively respond to these preconditions. Through identifying the (dis)affordances involved in such processes, we investigate co-production of user engagement with security apps. Drawing on observations and interviews with producers and users of apps, we explore the landscape of security apps as pervaded by processes of intended and actual (dis)affordances, sometimes also leading to abandonment of both use and users. A key finding is the divergence between the intended purposes of these apps – often framed around broad security ambitions – and their actual use, which frequently intertwines with mundane routines and logistical needs. This divergence paradoxically legitimizes broader securitisation discourses, even as the apps’ “successful use” often reflects a relatively privileged everyday life distant from tangible threats, highlighting the complex interplay between market forces, user practices, and the normalisation of surveillance.